2010
DOI: 10.1016/j.gie.2010.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of endoscopic spray cryotherapy for Barrett's esophagus with high-grade dysplasia

Abstract: Background Endoscopic ablation to treat Barrett’s esophagus (BE) with high-grade dysplasia (HGD) is associated with a decreased incidence of esophageal adenocarcinoma. Endoscopic spray cryotherapy (CRYO) demonstrates promising preliminary data. Objective To assess the safety and efficacy of CRYO in BE with HGD. Design Multicenter, retrospective cohort study. Setting Nine academic and community centers; treatment period, 2007 to 2009. Patients Subjects with HGD confirmed by 2 pathologists. Previous EMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
144
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(151 citation statements)
references
References 16 publications
(17 reference statements)
3
144
0
4
Order By: Relevance
“…Th is recommendation may change as further data become available. Promising cohort data on cryotherapy demonstrate high rates of CEIM and neoplasia ( 167,168 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Th is recommendation may change as further data become available. Promising cohort data on cryotherapy demonstrate high rates of CEIM and neoplasia ( 167,168 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Short term studies have shown a safety and efficacy profile similar to other ablative techniques (171)(172)(173). In a single center study with 32 patients, complete eradication (CE) of HGD was 100 %, and CE of IM was 84 % at 2-year follow-up.…”
Section: Cryotherapymentioning
confidence: 94%
“…The best available evidence is provided from cohort studies. A retrospective cohort study of 96 patients with BE with HGD treated with liquid nitrogen cryotherapy showed that 97% achieved complete eradication of HGD (CE-HGD), 87% had CE-D, and 57% had CE-IM (55). A small study of 32 patients designed to assess the long-term (2 year follow up) safety and efficacy of spray cryotherapy (liquid nitrogen) for BE with HGD demonstrated 100% CE-HGD and 84% CE-IM at 2-year follow-up, with recurrent HGD noted in 16% of patients (56).…”
Section: Cryotherapymentioning
confidence: 99%